A New Perspective of Migraine Symptoms in Patients With Congenital Heart Defect. Issue 10 (16th November 2018) - Liu, Yinglu; Li, Sulei; Wang, Rongfei; Han, Xun; Su, Min; Cao, Xiutang; Wang, Guangyi; Cao, Feng; Yu, Shengyuan
Abstract : Objective: To investigate the association between congenital heart defects (CHDs) and migraine and evaluate the efficacy of transcatheter defect closure from a new perspective. Methods: The patients with CHDs who underwent transcatheter defect closure were screened in the medical database of Chinese PLA General Hospital from January 2006 to January 2017. The assessment included basic admission information, the 3‐item ID Migraine Screener, and a detailed questionnaire administered by telephone or in an outpatient clinic. Patients were divided into ventricular septal defect (VSD) group and AP group (ie, patients with ASD or PFO) based on the type of defects. The latter group could be further divided into right‐to‐left shunt (RLS) group and left‐to‐right (LRS) shunt group. Each group contained 4 subgroups according to their migraine diagnosis before and after defect closure: persistent migraine (PM), relieved migraine (RM), without migraine (WM), and new‐onset migraine (NM). Results: The study recruited total 441 CHDs patients. Most patients in RLS group had migraine before and/or after surgery (76.4%, 42/55) and the proportion of them in NM group was higher than that of in LRS group (23.5%, 4/17 vs 6.8%, 18/266, P = .0418). Although the size of closure device or defect did not show significant differences, the ratios ( R = size of closure/size of defect) were significantly higher in NM group than those in WM group (1.40 [1.26, 1.80] vs 1.22 [1.13, 1.38] in AP group, P = .00238; 1.38 [1.23, 1.50] vs 1.22 [1.13, 1.37] in LRS group, P = .024934, respectively). Further logistic regression analysis illustrated that larger R value was a risk factor for NM in AP group (OR 1.48, 95% CI 1.07–2.05, P = .0188). Besides, migraine symptoms decreased significantly after defect closure in PM group among patients with ASD and PFO. Conclusion: This study revealed several associations between migraine and CHDs, especially the large ratio of closure device size to defect size. High‐quality randomized controlled trials and animal studies are needed to further investigate and clarify the underlying association between CHDs and migraine.